PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII1 SMP NEGERI 4 TANAH PUTIH - Susanti, Yeni; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievement of social studies SMP N 4 Tanah Putih fourth graderes still low with an average value of 67.83 and minimum completenness criteria (KKM) social studiesis 75. Between students, amounting to 18 people only 6 students who achieve classical KKM with 33.33%. This research is classroom action research (CAR), which aims to improve the student achievement of social studies class VIII1 at SMP N 4 Tanah Putih with implementation cooperative learning model type Think Pair Share (TPS). Formulation of the problem : is the implementation of cooperative learning model type Think Pair Share (TPS) can improve students achievement of social studies at SMP N 4 Tanah Putih. The research was conducted on February 01, 2016 ‘to February 22, 2016 by 2 cycles. Subjects werw students of SMP N 4 Tanah Putih, totaling 18 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 67.83. In the first cycle improve an average of 79.17 and an improve in the second with an average 86.67. Activities of the teacher in the learning process in cycle of 53.57% and the second meeting improve to 67.87%. In the third cycle of the first meeting and the second meeting improveKeywords: Model cooperative learning TPS, Results Learning and Economi